Domestic Wastewater Piping Network Planning and Technology Recommendations for Wastewater Treatment Case Study: The Ambarita Area, Samosir Regency, North Sumatra - Diki Surya Irawan; Deffi Ayu Puspito Sari; Anggita Ariesta (Publikasi Indonesia, 2021)
Lake Toba is one of ten programs the Ministry of Tourism in the Republic Indonesia, as a priority tourism area because of its unique potential. The Ambarita is one of 16 villages that are priority areas in Simanindo Subdistrict, Samosir Regency. At present, the quality of Lake Toba's waters has been polluted, the pollution is caused by domestic waste water which is discharged directly without prior treatment. The purpose of this study is to plan a domestic wastewater pipeline network and recommendations for wastewater treatment plants with a centralized system in the Ambarita. This study uses a data analysis method by using a population projection approach with maximum capacity to be planned in the draft MasterPlan of Ambarita and literature study for WWTP technology recommendations. The results showed that the total discharge of wastewater in the Ambarita was 0,06495 m3/second and the results of laboratory tests showed the parameters that exceeded quality standard were free chlorine and fecal coli. Piping network planning in the Ambarita uses concrete type pipes with diameters of 100 mm, 125 mm, 150 mm, 200 mm and 250 mm. The selected Waste Water Treatment Technology recommended is anaerobic-aerobic biofilter technology with removal efficiency for fecal coli and free chlorine are 99.9% and 65%.